Persepsi Peternak Muslim dan Analisis Saddu Az-Zari’ah Tentang Keharaman Membantu Orang Mengonsumsi Babi - Dwiki Agung Rizki Saputro; Muhammad Hanif al Hakim (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
Breeding is an activity to breed and maintain livestock to benefit and obtain results from these activities. Pig farming business in Purwogondo Village is a form of muamalah activity which is supported by the availability of abundant feed and pens located far from community settlements. This study discusses the perception of Muslim farmers about the prohibition of helping people consume pork located in Purwogondo Village. This study aims to determine the perception of active and non-active pig farmers in Purwogondo Village about the prohibition of helping people consume pork. This research is a field research, using a deductive approach and descriptive analysis. Sources of research data using books, journals, articles, related interviews. The research location is in Purwogondo Village, Kartasura Village, Kartasura District, Sukoharjo Regency. Data collection techniques in this study were interviews and documentation. The results shows that the pig farming business carried out by Muslim residents in Purwogondo Village is caused by several factors such as the economy, environment and lack of religious awareness. The reasons that encourage non-active pig farmers in Purwogondo Village to stop raising livestock are their own will to be supported by others, feelings of shame about the smell of the cage and fear of contracting the virus from pigs. Pig farming in Purwogondo Village is an activity that must be prevented because it is included in saddu az-zari'ah, which leads to a larger mafsadah.